The general form is just the foiled out version of the standard form. So using your standard form. We find:

(x-\frac{1}{11})^2+y^2=\frac{1}{121} x^2-\frac{2}{11} x + \frac{1}{121} +y^2=\frac{1}{121} x^2-\frac{2}{11} x +y^2=0

x^2-\frac{2}{11} x +y^2=0

Well, attempting to write that as code didn't work, how did you do that?

Here is the non coded version

(x-1/11)^2+y^2=1/121

x^2-2x/11+1/121+y^2=1/121

x^2-2x/11+y^2=0

so note, general form will always equal zero. Here, they cancel nicely, in others you will have your non-variable terms combined on the left side.

Let me know if you have any questions :)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up